2020
DOI: 10.3390/nano10030520
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Nanodevices

Abstract: Over the last decade, novel materials such as graphene derivatives, transition metal dichalcogenides (TMDs), other two-dimensional (2D) layered materials, perovskites, as well as metal oxides and other metal nanostructures have centralized the interest of the scientific community [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Many other studies have also displayed the patterning of metallic NPs, single-walled nanotubes (SWNTs), graphene indium tin oxide (ITO), and MXene into flexible, large-area, and arbitrary-shape structures with unique functionality to produce TCE. [403][404][405]…”
Section: Optoelectronicsmentioning
confidence: 99%
“…Many other studies have also displayed the patterning of metallic NPs, single-walled nanotubes (SWNTs), graphene indium tin oxide (ITO), and MXene into flexible, large-area, and arbitrary-shape structures with unique functionality to produce TCE. [403][404][405]…”
Section: Optoelectronicsmentioning
confidence: 99%
“…The optical limiting of ND suspension is mainly originated from the nonlinear scattering, nonlinear absorption, and nonlinear refraction [37,38]. Now, diverse materials have been suggested that could be used for photonics and optoelectronic devices [26,[39][40][41]. However, the field is still seeking new ways to produce easier and cost effective fabrication processes as well as high reliable and nontoxic nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms and intricacies related to the optical properties of solid-state materials opens the door towards applications in optoelectronic devices, [1,2] photosensors, [3][4][5] and bioimaging [6][7][8] and is therefore of broad interest for chemists, physicists, and material scientists alike. Notably, significant advances have been made in the field of luminescent organic solid-state materials.…”
Section: Introductionmentioning
confidence: 99%